Thermal characterization of an ultrasonic density-measurement cell - Higuti, Ricardo Tokio; Galindo, Bruno Shintate; Kitano, Claudio; Buiochi, Flavio; Adamowski, Julio Cezar (Institute of Electrical and Electronics Engineers (IEEE), 2007)
An ultrasonic density-measurement cell is experimentally characterized as a function of temperature. The measurement of propagation velocity and density of several liquids is performed in the 15 degrees C-40 degrees C temperature range. Results are compared to the tabulated values in the case of distilled water, showing an accuracy of 0.07% for the propagation velocity. The cell was tested with distilled water, alcohol, and homogenized milk, and density values are compared to those obtained with a pycnometer, showing 0.2% accuracy in density measurement for stabilized temperature and 0.4% accuracy under thermal gradient conditions.
Keywords: density; liquid propertiesi measurement cell; temperature; ultrasonic; velocity